2019
DOI: 10.21273/jashs04525-18
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Balance and Regulation in Tomato Genotypes of Different Color

Abstract: ADDITIONAL INDEX WORDS. anthocyanins, polyphenols, flavonoids, PSY ABSTRACT. Antioxidants, antioxidant capacity, and the expression of isoprenoid metabolism-related genes and two pigmentation-related transcription factors were studied in four native and four hybrid tomato (Solanum lycopersicum) genotypes with different-colored fruit. Red fruit genotypes were associated with greater lycopene, b-carotene, lipophilic antioxidant capacity, and greater chromoplast-specific lycopene b-cyclase (CYC-B) transcript leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
(51 reference statements)
3
10
0
Order By: Relevance
“…Lycopene was the most abundant carotenoid on fresh mass basis (56.2−179.4 µg/g) followed by β-carotene (0.2−20.5 µg/g). These results are similar to previous reports of red tomato extracts ( 40 , 41 ). Significant differences between treatments were observed; the treatment with the highest carotenoid mass fraction was treatment 3 (genotype=209, sonication=yes, enzyme=yes, solvent=isopropyl acetate), which is in line with our spectrophotometric results presented in experiment 3.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Lycopene was the most abundant carotenoid on fresh mass basis (56.2−179.4 µg/g) followed by β-carotene (0.2−20.5 µg/g). These results are similar to previous reports of red tomato extracts ( 40 , 41 ). Significant differences between treatments were observed; the treatment with the highest carotenoid mass fraction was treatment 3 (genotype=209, sonication=yes, enzyme=yes, solvent=isopropyl acetate), which is in line with our spectrophotometric results presented in experiment 3.…”
Section: Resultssupporting
confidence: 93%
“…In the literature, it is possible to find very wide ranges of lycopene and β-carotene contents in cherry tomatoes or native tomatoes. Recent works have reported lycopene mass fractions in Mexican native cherry tomatoes in a range of 44−82 µg/g ( 7 , 41 ). Vela-Hinojosa et al ( 41 ) also reported a β-carotene content between 1.4 and 3.0 µg/g in cherry red native tomatoes.…”
Section: Resultsmentioning
confidence: 99%
“…Tomatoes are known for their obvious red colour. This red colour is due to the accumulation of a carotenoid pigment that is the lycopene in the flesh and peel of tomato fruit (Vela-Hinojosa et al 2019, Sharma et al 2020. Tomato fruit is a rich source of energy, carotenoids (lycopene, carotene and xanthop hylls), flavonoids, p henolics, minerals, vitamin C, vitamin E, dietary fibers and other phytochemicals with a proven beneficial effect on human health (Rao and Rao 2007, Olaniyi et al 2010, Ramesh et al 2021a, 2021b.…”
Section: Importance Of Tomato Fruitmentioning
confidence: 99%
“…Tomatoes vary in size, shape, and color. As the tomato ripens, the color changes depending on the genotype, and, depending on the color, it has various antioxidant functions [2,3].…”
Section: Introductionmentioning
confidence: 99%